Ice Through Inuit Eyes, Cape Dorset - Gita Laidler; Gita Laidler (Polar Data Catalogue, 2013)
The dataset includes interview transcripts; focus group audio files; interview and sea ice trip video; interview, focus group, and sea ice trip photos; interview maps; and GPS tracks from sea ice trips. Data was generated from interviews and focus groups with Inuit elders and hunters. Textual data stored in Microsoft Word documents. Digital audio data stored in Sony Digital Voice Recorder (DVF) format and Waveform audio format (WAV). Digital video data stored in Windows Media Video (WMV), Audio Video Interleave (AVI), Motion Picture Experts Group (MPEG), and Digital Video Disc (DVD) format. Digital photos stored in Joint Photographic Experts Group (JPEG) format. Maps stored in hard copy (mylar overlays for paper maps) and digital formats inlcuding: ESRI ArcGIS project files (MXD) and shapefiles (SHP). GPS tracks are stored in GPS eXchange Format (GPX) and Garmin propietary format.